STRATEGIC SYNERGY OR REGULATORY RIDDLE? EVALUATING THE MERGER AND ACQUISITION LANDSCAPE OF PSU BANKS IN INDIA - Ajay Singh,Dr. Geeta Ravish (Journal of Computational Analysis and Applications (JoCAAA), 2024)
In the modern world of the 21st century when the whole world is moving towards globalizationand digitalization The Indian economy is a developing economy and to give a boost to its “Big Banks”needed and part of its merger of PSU banks had happened. Recently Mega-Merger in the banking sectorresults in the 12 banks becoming four banks now.